Manufacturing Automation for Magnesium Die Casting - Vanli, Ali Serdar; Akdogan, Anil (SPRINGER-VERLAG BERLIN, 2019)
High pressure die casting (HPDC) of magnesium alloy parts is mostly problematic. Because magnesium alloys oxidize at above 400 degrees C. They need to be protected by the proper gas atmospheres during manufacturing. Besides, other components of an integrated HPDC cell such as casting machine, melting-dosing unit, gas mixing system and die heating-cooling device must be carefully designed in order to obtain the desired high quality products. This work guides to design manufacturing automation of HPDC process in order to get succeeded results in product quality. It also details the manufacturing parameters like gate velocity and intensification pressure for better quality parts. The collected big data about manufacturing analyzed as computer aided quality parameters which were used for continuous improvement of the process. The obtained data from the manufacturing process was used to increase the product quality expectations like high density and satisfactory mechanical properties. At the end of the conducted manufacturing experiments at our industrial scale die casting cell the required quality values were obtained.
Keywords: High pressure die casting; Magnesium alloys; Big data; Product quality; Engineering